2010
DOI: 10.1007/s10584-010-9901-y
|View full text |Cite
|
Sign up to set email alerts
|

Impact of recent climatic change on growth of low elevation eastern Mediterranean forest trees

Abstract: Evidence is presented of how Pinus halepensis Miller from dry habitats at <300 m elevation of four Greek island regions have responded to climatic conditions of the last two centuries. We compared historical periods of low growth due to low precipitation with the recent period of significant precipitation decline. In all cases trees' growth patterns across the twentieth century were consistent with trends in annual (rather than seasonal) precipitation, with lowest values in both precipitation and radial growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
47
2
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(64 citation statements)
references
References 48 publications
8
47
2
3
Order By: Relevance
“…6) shows that there is a statistically significant trend towards narrower tree-rings after the 1970s, but the trend lessens and is no longer significant after 2000 and is not found for the most recent years. This differs from results of Sarris et al (2011) on Pinus halepensis growing in lowland Crete, who distinctly showed that tree-ring widths have decreased since the 1970s in connection with the diminution in rainfall and stated that trees have increased their dependency towards deep water reserves. In this respect, our preliminary findings highlight the capacity of Z. abelicea to cope with increasing summer drought conditions.…”
Section: Stability Of Climatic Sensitivity Through Timecontrasting
confidence: 95%
See 1 more Smart Citation
“…6) shows that there is a statistically significant trend towards narrower tree-rings after the 1970s, but the trend lessens and is no longer significant after 2000 and is not found for the most recent years. This differs from results of Sarris et al (2011) on Pinus halepensis growing in lowland Crete, who distinctly showed that tree-ring widths have decreased since the 1970s in connection with the diminution in rainfall and stated that trees have increased their dependency towards deep water reserves. In this respect, our preliminary findings highlight the capacity of Z. abelicea to cope with increasing summer drought conditions.…”
Section: Stability Of Climatic Sensitivity Through Timecontrasting
confidence: 95%
“…This study is innovative for Crete and presents a challenge, as very little dendroclimatological research has been carried out on the island (e.g. Sarris et al, 2011;Touchan et al, 2014, both focused on Pinus halepensis subsp. brutia).…”
Section: Introductionmentioning
confidence: 99%
“…Observational evidence of shifts in forest structure and function over the last century has started to accumulate and are frequently attributed to climatic changes. Tree growth changes related to temperature increase (Jump et al 2006;Linares and Tíscar 2010), decline in precipitation (Sarris et al 2011) and/or CO 2 fertilisation (Martínez-Editor: Will Steffen.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing drought events correlate with increased tree mortality that coincides with severe fire outbreaks (Sarris et al 2011). …”
Section: Introductionmentioning
confidence: 99%